Sovereign credit ratings in South Africa: Does institutional quality matter? - Mundonde, Justice; Takawira, Oliver (The Economics and Finance Letters, 2025)
The study aimed to empirically assess whether governance quality influences sovereign credit scores in South Africa. The country faces a significant infrastructure financing gap that requires not only public sources but also the issuance of securities on global capital markets. Consequently, sovereign credit scores are a critical component of South Africa’s development finance discourse. An Autoregressive Distributed Lag (ARDL) framework was applied to credit scores from Fitch, Standard & Poor’s, and Moody’s. The ARDL model is advantageous because it is efficient in both small and finite samples. Data for economic indicators were collected over 23 years, ending in 2023. Institutional quality was evaluated using governance indicators reported by the World Bank. The evidence indicates that, individually, corruption, politics, governance, freedom of expression, lawfulness, and regulatory quality do not significantly influence credit scores in South Africa. Variations in gross domestic product (GDP) and foreign investor activities also have an insignificant impact on ratings. In South Africa, sovereign scores are influenced by the reserves-to-external-debt ratio, the current account balance to GDP ratio, and inflation. From a policy perspective, although governance variables are individually insignificant, the government of South Africa should aim to improve institutional quality. Even though governance variables do not directly enhance credit scores, they reduce the likelihood of sovereign downgrades. Further research could explore whether governance variables collectively determine ratings in South Africa. The study could be expanded by including a broader sample that encompasses the least developed economies, thereby improving the generalizability of the results.